Standardized Incidence Rate, Risk and Survival Outcomes of Second Primary Malignancy Among Renal Cell Carcinoma Survivors: A Nested Case-Control Study - Wang, Zhixian; Yin, Yisheng; Wang, Jing; Zhu, Yunpeng; Li, Xing; Zeng, Xiaoyong (Frontiers in Oncology, 2021)
Purpose: Second primary malignancy (SPM) is challenging for treatment and long-term survival. We sought to investigate the standardized incidence rate (SIR), risk factors, and survival outcomes for SPM after renal cell carcinoma (RCC) treatment. Method: A nested case-control study was designed, we identified all T1-4N0-1M0 RCC patients diagnosed between 2004 and 2015 in the Surveillance, Epidemiology, and End Results database and followed them for SPM diagnosis for up to 13 years. Patients with SPM diagnosis ≥6 months after treatment of primary T1-4N0-1M0 RCC were identified as the case cohort and SPM-free patients were the control cohort. SIRs and the excess risk were calculated. A competing risks and Cox model were used to evaluate the risk factors of SPM and overall survival (OS). Results: A cohort of 6,204 RCC patients with SPM were matched with a control group of 31,020 RCC patients without SPM. The median time-to-SPM interval was 54.5 months in RCC patients with SPM diagnosis. Besides, an SPM of T3/4 or/and M1 stage diagnosis was positively associated with a longer time-to-SPM interval. SIR of SPM increased by follow-up time and decreased with age at diagnosis (Pfor all <0.001). SPM in the kidney had the highest SIR (54.6, P <0.001) among all SPMs. Prostate cancer (29.8%) in males and breast cancer (23.5%) in females were the most common SPM. Older age, black ethnicity, male sex, higher family income, papillary RCC, and lower TNM stage were significant risk factors for SPM diagnosis. The proportion of deaths from SPM exceeds that of deaths from RCC 3 years after the first RCC treatment. Patients with SPM and early time-to-SPM interval shortens the OS compared with SPM-free patients. The 5-year OS was 85.9% and 58.9% from the first RCC and the SPM diagnosis, respectively. Besides, patients with low-grade/early-stage SPM could benefit from aggressive surgical treatment for solid tumors. Conclusions: Collectively, our study described the epidemiological characteristics of SPM among RCC survivors and identified the independent predictors of the SPM diagnosis and its survival outcomes. This study highlights the importance of patient education and follow-up after the surgery for RCC.